DESIGN MOLDING MUG TUPPERWARE MENGATASI SHORT SHOT PRODUK INJECTION PLASTIK - Mochammad Muchid; Heru Tjahjono (PROSIDING SNAST, 2018)
Before determining the product is produced then 3D & 2D modeling, analysis, physical prototype, open tooling, trial tooling, product initial, release drawing 3D & 2D, product, CAD (Computered Aided Design) is required and product analysis. To support the process is used SolidWork software. the outline of molding injection is divided into 2 parts, namely: core and cavity, cores are used to form part of the product and cavity is used to form the outside of the product. Injection molding is the most commonly used manufacturing process printing products of various materials used. This TupperWare product without using cover with PP material. Plastic weight 21.82gr, volume 23.83cm3. using manual mesh with triangle size15.000 obtained triangels number 512, and pointer diameter 3mm (hole nozzle) then for filling time give auto, melt temperature 230 ° C, condition temperature molding 50 ° C, injection pressure limit 100Mpa. Then obtained for the material removal process is 0.569 seconds, with a pressure strength of 32.60Mpa, with a defective product Sinkmark 0.0072mm there radius section, 0.0130mm located in the Injection Area, there are also defects Air Trap product (air trapped) on the radius flatten for 0.569 ° C. Obtained a height total molding TupperWare 263mm with a weight of 55.649Kg.